Altered frontal electroencephalography as a potential correlate of acute dissociation in dissociative disorders: novel findings from a mirror confrontation study. Issue 6 (10th November 2022) - Schäflein, Eva; Mertens, Yoki Linn; Lejko, Nena; Beutler, Sarah; Sattel, Heribert; Sack, Martin
Abstract : People suffering from chronic dissociation often experience stress and detachment during self-perception. We tested 18 people with dissociative disorders not otherwise specified (DDNOS; compared with a matched sample of 18 healthy controls) undergoing a stress-inducing facial mirror confrontation paradigm, and measured acute dissociation and frontal electroencephalography (measured with a four-channel system) per experimental condition (e.g. confrontation with negative cognition). Linear mixed models indicated a significant group×time×condition effect, with DDNOS group depicting less electroencephalography power than healthy controls at the beginning of mirror confrontation combined with negative and positive cognition. This discrepancy – most prominent in the negative condition – diminished in the second minute. Correlational analyses depicted a positive association between initial electroencephalography power and acute dissociation in the DDNOS group. These preliminary findings may indicate altered neural processing in DDNOS, but require further investigation with more precise electroencephalography measures.